ChemInform Abstract: Free‐Radical Hydroxymethylation of Ketimines Generated in situ: A One‐Pot Multicomponent Synthesis of β, β‐Disubstituted‐β‐aminoalcohols. Issue 15 (25th March 2013) - Rossi, Bianca; Pastori, Nadia; Clerici, Angelo; Punta, Carlo
Abstract Oxidative radical addition of methanol and aromatic amines to simple aliphatic ketones offers a novel synthesis of β, β‐disubstituted‐β‐aminoalcohols.